Back Cover: Near‐Infrared‐Light‐Driven Artificial Photosynthesis by Nanobiocatalytic Assemblies (Chem. Eur. J. 13/2014). Issue 13 (24th March 2014) - Lee, Joon Seok; Nam, Dong Heon; Kuk, Su Keun; Park, Chan Beum
<x xml:space="preserve">Abstract</x> Upconversion has been applied to near‐infrared (NIR)‐light‐driven artificial photosynthesis. For the development of an artificial photosynthetic platform that mimics natural photosynthesis in green plants, it is critical to harvest NIR‐range light, which constitutes over 46% of the solar energy. In their Communication on page 3584 ff., C. B. Park and co‐workers successfully utilize Förster resonance energy transfer between upconversion nanoparticles and organic photosensitizers for efficient photon conversion and photosynthesis under NIR light.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>